2014
DOI: 10.3944/aott.2014.14.0177
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severe postoperative pain in patients with total hip arthroplasty

Abstract: Patients with severe anxiety, depression and Type D personality appear to be at risk of developing severe postoperative pain. In addition, female gender and the intensity of pain immediately after procedure were found to be important risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 38 publications
1
36
1
Order By: Relevance
“…These factors are enhanced in healthy women and are relevant for acute as well as chronic pain after surgery [1]. Recent studies further confirm these observations [94,95 & ] and stress the importance of psychological factors in postoperative pain [26,[96][97][98]. Thus, psychological factors might be the actual contributors to increased pain, both acute and chronic, after surgery rather than female gender.…”
Section: Possible Confounders For Gender Differencesmentioning
confidence: 63%
See 1 more Smart Citation
“…These factors are enhanced in healthy women and are relevant for acute as well as chronic pain after surgery [1]. Recent studies further confirm these observations [94,95 & ] and stress the importance of psychological factors in postoperative pain [26,[96][97][98]. Thus, psychological factors might be the actual contributors to increased pain, both acute and chronic, after surgery rather than female gender.…”
Section: Possible Confounders For Gender Differencesmentioning
confidence: 63%
“…With regard to gender aspects, recent studies on patients submitted to hip or knee arthroplasty yielded inconsistent results. In one study (n ¼ 90), female gender (OR ¼ 4.9), as well as anxiety (OR ¼ 6.0) and depression (OR ¼ 7.3), among other factors, were highly associated with severe acute postoperative pain after total hip arthroplasty [26]. In another study (n ¼ 102), women showed a longer duration of postoperative pain within the first 6 weeks after open or arthroscopic rotator cuff repair (33 vs. 26 days in men, P ¼ 0.03), but prevalence of residual pain did not significantly differ (62 vs. 41%, P ¼ 0.11) [27].…”
Section: Orthopedic Surgerymentioning
confidence: 97%
“…Even though depressive symptoms predict worse pain scores in most surgical populations, the target domains are usually activity interference and pain severity, but not perception of care. 28,29 The findings point out important differences in pain perception between surgical populations that need consideration when measuring the outcomes of new care plans.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown to adversely affect the postoperative pain and bring enormous suffering to patients [6][7][8][9]. Although increasing clinical evidence has demonstrated the positive correlation between anxiety and pain during the perioperative period [5,7], few laboratory studies were conducted to investigate this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative anxiety is very common in patients undergoing surgery, with an incidence of 60 to 92 % [2,4,5]. Many studies have shown the positive correlation between preoperative anxiety and postoperative pain intensity as well as analgesic consumption [5][6][7][8][9]. The phenomenon that exposure to physical or psychological stressors can enhance nociception and pain sensitivity is described as stress-induced hyperalgesia (SIH) [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%